Genomic analysis of P elements in natural populations of Drosophila melanogaster. - Bergman, C.M.; Han, S.; Nelson, M.G.; Bondarenko, V.; Kozeretska, I. (PeerJ, 2017)
The Drosophila melanogaster P transposable element provides one of the best cases of horizontal transfer of a mobile DNA sequence in eukaryotes. Invasion of natural populations by the P element has led to a syndrome of phenotypes known as P-M hybrid dysgenesis that emerges when strains differing in their P element composition mate and produce offspring. Despite extensive research on many aspects of P element biology, many questions remain about the genomic basis of variation in P-M dysgenesis phenotypes across populations. Here we compare estimates of genomic P element content with gonadal dysgenesis phenotypes for isofemale strains obtained from three worldwide populations of D. melanogaster to illuminate the molecular basis of natural variation in cytotype status. We show that P element abundance estimated from genome sequences of isofemale strains is highly correlated across different bioinformatics approaches, but that abundance estimates are sensitive to method and filtering strategies as well as incomplete inbreeding of isofemale strains. We find that P element content varies significantly across populations, with strains from a North American population having fewer P elements but a higher proportion of full-length elements than strains from populations sampled in Europe or Africa. Despite these geographic differences in P element abundance and structure, neither the number of P elements nor the ratio of full-length to internally-truncated copies is strongly correlated with the degree of gonadal dysgenesis exhibited by an isofemale strain. Thus, variation in P element abundance and structure across different populations does not necessarily lead to corresponding geographic differences in gonadal dysgenesis phenotypes. Finally, we confirm that population differences in the abundance and structure of P elements that are observed from isofemale lines can also be observed in pool-seq samples from the same populations. Our work supports the view that genomic P element content alone is not sufficient to explain variation in gonadal dysgenesis across strains of D. melanogaster, and informs future efforts to decode the genomic basis of geographic and temporal differences in P element induced phenotypes.